An unusual cause of gastrointestinal bleeding in an elderly patient - Köklü, Hayretdin; Dinçer, Anıl; Kumbasar, Ulaş; Doğrul, Ahmet Bülent; Purnak, Tuğrul (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Köklü H, Dinçer A, Kumbasar U, Doğrul AB, Purnak T. An unusual cause of gastrointestinal bleeding in an elderly patient. Turk J Gastroenterol 2018; 29: 610-2.